Effect of liveweight on the carcass traits of Pannon White growing rabbits - Szendrö Z.; Radnai I.; Biro-Németh E.; Romvári R. (Rabbit production in hot climates, 1994)
For 163 Pannon White growing rabbits of both sexes slaughtered at 12-13 wk of age at a body weight of 2.6, 2.6-2.7, 2.7-2.8, 2.8-2.9, 2.9-3.0 and 3 kg the average dressing percentage was 60.40, 61.07, 62.92, 61.58 and 61.32 per cent respectively. As compared to average weight gain of the body (28.1 per cent) between 2.6 and 3 kg, full gastrointestinal tract (11.7 per cent), blood (22.8 per cent), head (23.8 per cent) and liver (24.7 per cent) were the slowest, whereas skin (45.1 per cent) and perirenal fat (94.7 per cent) were the fastest in gaining weight. Relative to liveweight and carcass weight, rabbits weighing 2.8-2.9 kg were classified as of best slaughter value.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)